Instructor Attitudes within the SCALE Efficiency Projects - Lanny Arvan; Diane Musumeci (Online Learning, 2019)
This paper presents the results of interviews with the principal investigators of the current Sloan Center for Asynchronous Learning Environments (SCALE) Efficiency Projects. There are six such projects: Spanish, Microbiology, Economics, Math, Chemistry, and Physics. The paper reviews each project individually, summarizes the results, and then discusses some common lessons learned as well as some still open issues. The paper considers satisfaction both from the perspective of the course director/designer and from the perspective of other instructors and graduate teaching assistants. The evidence appears to show that all of these groups are satisfied with ALN, relative to the prior situation. Nonetheless, it is not clear whether these results would translate to other high enrollment courses.